Economic and environmental feasibility of replacing liquefied petroleum gas from the recovery of heat generated in the production of compressed air (Research, Society and Development, 2020)
Several companies use liquefied petroleum gas (LPG), commonly known as “cooking gas” to heat the water in the dressing room showers. The use of LPG for this purpose represents a high cost, however, companies that have a compressed air production system could recover the heat generated in the process of compressing atmospheric air and use it as a substitute for LPG for heating water, reducing costs and environmental impacts. In this sense, the objective was to analyze the economic and environmental viability of recovering the heat generated in the production of compressed air to replace LPG for heating shower water in a chemical industry in the state of Minas Gerais. Initially, the costs of consuming LPG for heating showers and implementing the project to recover the heat produced by the compressors were budgeted. The results of this feasibility study showed that the implementation of this type of heat recovery system produced during the compression of compressed air is economically viable. In addition, this replacement would promote an increase in the global energy efficiency of this industry, as well as a reduction in CO2 emissions. This analysis also demonstrated that the inclusion of this type of heat recovery installation in the initial design can influence the location of the compressors, reducing costs with thermal insulation and pipes and increasing the efficiency of the recovery of the heat produced.